The nursing techniques and technologies - Maria Aparecida de Luca Nascimento (Rev Rene)
Professions are characterized by their technical elements. Thus, they are socially known and perpetuatedby their practices. With the nursing profession, it could not be different, and it is characterized by care actions. By considering that the nursing care process is multifaceted and multidimensional, and that severalsciences are focused on it, this care, due to the fact that it is provided to the human being, who is a social being,is underpinned by the biological, human and social sciences.